Quantum dot synthesis from waste biomass and its applications in energy and bioremediation - Ahuja, Vishal; Bhatt, Arvind Kumar; Varjani, Sunita; Choi, Kwon Young; Kim, Sang Hyoun; Yang, Yung Hun; Bhatia, Shashi Kant (Chemosphere, 2022)
Quantum dots (QDs) are getting special attention due to their commendable optical properties and applications. Conventional metal-based QDs have toxicity and non-biodegradability issues, thus it becomes necessary to search for renewable precursor molecules for QDs synthesis. In recent years, biomass-based carbon rich QDs (CQDs) have been introduced which are mainly synthesised via carbonization (pyrolysis and hydrothermal treatment). These CQDs offered higher photostability, biocompatibility, low-toxicity, and easy tunability for physicochemical properties. Exceptional optical properties become a point of attraction for its multifaceted applications in various sectors like fabrication of electrodes and solar cells, conversion of solar energy to electricity, detection of pollutants, designing biosensors, etc. In recent years, a lot of work has been done in this field. This article will summarize these advancements along in a special context to biomass-based QDs and their applications in energy and the environment.
Keywords: Carbon rich; Conventional metals; Energy; Environment; ITS applications; Optical applications; Precursor molecules; Quantum dot synthesis; Synthesised; Waste biomass; Biodegradation, Environmental; Biomass; Carbon; Quantum Dots; Solar Energy; Biomass; Biosensors; Energy; Environment; Quantum dots